Refining Our Understanding of Hypercompetition and Hyperturbulence - Zohar, Asaf; Morgan, Gareth (Organization Science, 1996)
The lead “Crossroads” essay by Kenneth Aupperle presents a strong case for the relevance of an ancient Greek story for the “new realities” faced by present-day organizations. Aupperle's story of the story of the “March Up Country” is intended to highlight the historical parallels of this remarkable event with current “hypercompetitive” conditions. He identifies some of the critical factors that contributed to the Greek army's successful organizational “reconfiguration” under the “hypercompetitive conditions” of war. Basically, his argument is that, by analogy, Hellenian culture, “was to individual city-states as a contemporary corporation is to its separate departments and strategic business units,” and that the episode offers useful insights into some of the critical ingredients necessary for meeting the challenges of current organizational conditions and circumstances.